Вікові зміни систолічної та діастолічної функції міокарда при хронічній серцевій недостатності у жінок з надлишковою масою тіла та ожирінням - Бідзіля, Петро Петрович (My University, 2015)
Досліджено вікові зміни систолічної та діастолічної функції міокарда при хронічній серцевій недостатності (ХСН) у жінок з надлишковою масою тіла та ожирінням. Встановлено, що зі збільшенням віку прогресує ХСН, яке проявляється підвищенням функціонального класу захворювання зниженням систолічної функції міокарда, формуванням легеневої гіпертензії та поширенням поєднання систолічної та діастоічної дисфункції лівого шлуночка. Найбільш виражені зміни притаманні жінкам старечої вікової групи Women are near 50 % of all patients with chronic heart failure (CHF). Next few years the CHF in women will reach 8 %, and in men only 3 %. In 40 years old the risk of CHF without old myocardium infraction is 1/6 in women and 1/9 in men. The aim of the work was the study of age-related changes of systolic and diastolic function of myocardium at CHF in women with overweight and obesity. Methods: there were examined 193 women of the different age groups with CHF of I–III functional class on the background of the normal, redundant body mass and abdominal obesity of I–III degree. The indices of systolic and diastolic function of myocardium were assessed by the method of echocardiography. Processing of the received data was carried out by the methods of non-parametric statistics. Results. There was established that with age in women with overweight and obesity takes place the progression of CHF that is demonstrated by the raise of the functional class of disease, lowering of the systolic function of myocardium, formation and progression of the pulmonary hypertension. There takes place I type of the diastolic dysfunction that is more evident in studied women of the senile age group. Conclusion: There was demonstrated the negative influence of an ageing on the functional state of myocardium at CHF in women with overweight and obesity.
Age-related changes of systolic and diastolic function at chronic heart failure in women with overweight and obesity
Keywords: хронічна серцева недостатність; жінки; ожиріння; систолічна, діастолічна функція; віковий фактор; chronic heart failure; women; systolic; diastolic function; obesity; age-related factor